Effectiveness of Antiplatelet Drug Loading before Acute-phase Coil Embolization of Ruptured Cerebral Aneurysms - Okuma, Yu; Shimazu, Yosuke; Hirotsune, Nobuyuki; Tanabe, Tomoyuki; Muraoka, Kenichiro; Sato, Yu; Hosomoto, Kakeru; Nishino, Shigeki (Journal of Neuroendovascular Therapy, 2018)
Objective: The hemostatic/coagulation capacity is enhanced in the acute phase of ruptured cerebral aneurysms, and the risk of thromboembolic complications during endovascular surgery is high. We examined the usefulness of antiplatelet drug loading (LD) before acute-phase coil embolization of ruptured cerebral aneurysms.Methods: The subjects were 117 patients who underwent acute-phase coil embolization of ruptured cerebral aneurysms in our hospital between June 2009 and October 2016. They were divided into three groups (non-administration, clopidogrel LD, and dual LD groups) based on the presence or absence of preoperative antiplatelet drug administration, and the incidence of thromboembolic events (TEEs), influence of combined adjunctive techniques (ATs), and incidence of hemorrhagic events were compared.Results: In the clopidogrel LD group, there was no significant decrease in the incidence of TEEs in comparison with the non-administration group. However, the incidence of TEEs was significantly lower in the dual LD group. Similarly, combined ATs significantly decreased the incidence of TEEs in the dual LD group. In LD groups, there was no increase in the incidence of hemorrhagic complications.Conclusion: The results suggest that dual LD decreases the incidence of TEEs. In the future, its effects should be further investigated.